THE IMPORTANCE OF THE PROPRIOCEPTIVE TRAINING AND ITS RESULTS IN JUNIOR HURDLE ATHLETES - Alecu Stefan; Ionescu Bondoc Dragos (Editura Universitatii Transilvania din Brasov, 2019)
: In this study we aim to demonstrate the fundamental role of proprioceptive training as an integral part of the junior sports training in the 110 m hurdle test. For this we subjected the tests, before and after the training period, using proprioceptive techniques and exercises to influence the hurdle runner technique in the two subjects chosen for this experiment, and the results obtained revealed their progress in within the parameters we considered relevant to the study. The aim of this study is to reveal the importance of proprioceptive training in correcting the technique of hurdle running, but also parameters that change and their value.